Wealth creation for expanding the middle class in the Philippines - Jose Ramon G. Albert; Roehlano M. Briones; John Paolo R. Rivera (Philippine Institute for Development Studies (PIDS), 2024)
The Philippines has set an ambitious goal of becoming a predominantly middle-class society free of poverty by 2040. However, this aspiration comes at a time of significant global headwinds that pose risks to the country's development trajectory. Growing the middle class is more closely related to new wealth creation rather than typically associated themes such as poverty reduction or redistribution. This background paper for the 2024 Philippine Institute for Development Studies Annual Public Policy Conference (APPC) provides an updated profile of the Philippine middle-class. Using an income-based definition that delineates the middle-class as households with per capita incomes between 2 to 12 times the official poverty line, the paper finds that the middle-class grew from 28.5% of the population in 1991 to 39.8% in 2021. However, this growth has not been linear, with the COVID-19 pandemic reversing some of the gains made in recent years. Drawing on data from the 2021 Family Income and Expenditure Survey and the July 2021 round of the Labor Force Survey, this paper describes the key socioeconomic characteristics of the middle-class. The middle-class is predominantly urban, more educated, and more engaged in formal employment compared to lower income groups. However, there are significant regional variations in the size and profile of the middle-class. To harness the potential of the middle-class as a driver of inclusive growth, this APPC background paper proposes a multi-pronged strategy that includes: (1) promoting social justice in natural resource management and climate change transition; (2) harnessing new opportunities in trade and investments for MSMEs; (3) ensuring a future-ready workforce and social protection; and (4) improving digital governance and public service delivery. This paper argues that realizing the vision of a predominantly middle-class society will require bold and concerted action across these priority areas. It will also necessitate effective leadership, coordination, and collaboration among government, the private sector, civil society, and development partners. By putting in place a comprehensive agenda for middle-class expansion, the Philippines can build a more resilient, equitable, and prosperous future for all Filipinos.
Keywords: 330; middle class; inclusive growth; Philippines; income distribution; poverty; social protection; digital economy; climate change; MSMEs